How Much Country Economy Influences ECC Profile in Serbian Children—A Macro-Level Factor Analysis - Markovic, Dejan; Soldatovic, Ivan; Vukovic, Rade; Peric, Tamara; Campus, Guglielmo Giuseppe; Vukovic, Ana (Frontiers in Public Health, 2019)
Introduction: Serbia has universal health coverage (UHC) for pediatric dental care and similar regional distribution of dentists and physicians per 1000 inhabitants. However, high prevalence of early childhood caries (ECC) with wide regional variation was observed in previous studies. This paper aimed to analyze the potential association between economic and healthcare regional macro level factors with prevalence, treatment, and consequences of ECC. Method: Data on ECC related oral health outcomes (caries prevalence, untreated caries, and presence of caries lesions on permanent first molars) were collected through cross-sectional pathfinder survey including all four statistical regions and eight administrative districts of Serbia. WHO Basic Methods for Oral Health Surveys stratified cluster sample analyzing 12 sites was used to determine caries prevalence. Furthermore, we added five additional sites in order to obtain adequate distribution of data regarding administrative districts, in order to analyze macro level impact. Data on macro level factors included regional information on various economic, population, and healthcare factors: gross domestic product (GDP), social and health care expenditures, local self-government funding, unemployment rate, population density, density of physicians and dentists. Results: Final sample included 1636 children, in two age groups: younger preschoolers aged 36 to 71 months and older preschoolers aged 72 to 91 months. Observed prevalence of ECC in children up to 71 months of age was 41.1%, and prevalence of caries in the older preschooler group was 76.7%. Of these, 90.3% had untreated caries. Furthermore, 11.1% of examined older preschoolers already had lesions on permanent first molar. All ECC related oral health outcomes were statistically significantly associated with regional social economic indicators – poor oral health was more frequently observed in regions and districts with lower economic performance. Conclusions: This study, performed in a nationally representative sample of preschool children, revealed a highly statistically significant association of economic macro level factors with caries prevalence, (non)treatment, and consequences of ECC. These findings suggest that the most of public-health efforts regarding prevention and early treatment of ECC should be directed at regions with lower economic performance.